Spatial distribution of soil iron across different plant communities along a hydrological gradient in the Yellow River Estuary wetland - Liu, Xue; Sun, Dandan; Qin, Jifa; Zhang, Jiapeng; Yang, Yunfei; Yang, Jisong; Wang, Zhikang; Zhou, Di; Li, Yunzhao; Wang, Xuehong; Ning, Kai; Yu, Junbao (Frontiers in Ecology and Evolution, 2022)
Iron is an important element and its biogeochemical processes are vital to the matter and energy cycles of wetland ecosystems. Hydrology greatly controls characteristics of soil property and plant community in wetlands, which can regulate the behavior of iron and its oxides. However, it remains unclear how the spatial distribution of iron and its forms in estuarine wetlands responses to hydrological conditions. Five typical plant communities along a naturally hydrological gradient in the Yellow River Estuary wetland, including Phragmites australis in freshwater marsh (FPA), Phragmites australis in salt marsh (SPA), Tamarix chinensis in salt marsh (TC), Suaeda salsa in salt marsh (SS) and Spartina alterniflora in salt marsh (SA), as sites to collect soil samples. The total iron (FeT) and three iron oxides (complexed iron, Fep; amorphous iron, Feo; free iron, Fed) in samples were determined to clarify the spatial distribution of iron and explore its impact factors. The mean contents of FeT, Fep, Feo and Fed were 28079.4, 152.0, 617.2 and 8285.3 mg·kg-1 of soil at 0-40 cm depth in the different sites, respectively. The means were significantly different across communities along the hydrological gradient, with the higher values for SA on the upper intertidal zone and for SPA on the lower intertidal zone, respectively. Iron and its forms were positively correlated with the total organic carbon (TOC), dissolved organic carbon (DOC), total nitrogen (TN) and clay, and negatively correlated with electrical conductivity (EC). The indexes of iron oxides (Fep/Fed, Feo/Fed and Fed/FeT) were also different across communities, with a higher value for SA, which were positively correlated with soil water content (WC) and TOC. The results indicate that a variety of plant community and soil property derived from the difference of hydrology might result in a spatial heterogeneity of iron in estuarine wetlands.